Seldjukides de Rūm contre Horde d’Or : l’expédition de Crimée d’après Ibn Bībī (vers 1225) - Michel Balivet; Homa Lessan Pezechki (Revue des Mondes Musulmans et de la Méditerranée)
This study analyses a critical phase of the 13th-century economic and commercial war between the Turkish Sultanate of Anatolia, the Golden Horde, the Russian principalities, and the Qipchaqs. By translating the work of Ibn Bībī, a Persian author from the Seljūq period who narrated the Seljūq expedition to Crimea, we will highlight both the causes and the consequences of the temporary occupation of the large port of Sudak in the aftermath of the military expedition.